Home as Found : Authority and Genealogy in Nineteenth-Century American Literature - Sundquist, Eric J. (Book collections on Project MUSE., 1979)
Eric Sundquist takes four representative writers--James Fenimore Cooper, Henry David Thoreau, Nathaniel Hawthorne, and Herman Melville--and considers the way in which each grapples with the crucial issues of genealogy and authority in his works. From all four a common pattern emerges: the desire to revolt against the past is countered by the need to invoke or even repeat it. Sundquist's approach to the texts is psychoanalytic, but he does not attempt a clinical dissection of each writer; rather, he determines how personal crisis became material for engaging with larger questions of social and literary crisis.